Predictors of burnout among academic family medicine faculty: Looking back to plan forward - Viola Antao; Paul Krueger; Christopher Meaney; Jeffrey C. Kwong; David White (PLoS ONE, 2026)
Objective To identify the prevalence and predictors of burnout among academic family medicine faculty. Design A comprehensive survey of academic family medicine faculty on burnout, perceptions of work life, and practice in 2011. Setting A large, distributed Department of Family and Community Medicine at the University of Toronto. Participants All 1029 faculty members were invited to participate. Main outcome measures Maslach Burnout Inventory three subscales (emotional exhaustion, depersonalization, personal accomplishment). Results The survey response rate was 66.8% (687/1029). The prevalence of high emotional exhaustion scores was 27.0% and high depersonalization was 9.2%, whereas the prevalence of high personal accomplishment scores was 99.4%. Bivariate analyses identified 27 variables associated with emotional exhaustion and 18 variables associated with depersonalization, including: ratings of the practice setting; leadership and mentorship experiences; job satisfaction; health status; and demographic variables. Multivariate analyses found four predictors of emotional exhaustion: lower ratings of job satisfaction, poorer ratings of workplace quality, working ≥50 hrs/week, and poorer ratings of health status. Predictors of depersonalization included lower ratings of job satisfaction, ≤5 years in practice, lower ratings of health status, and poor ratings of mentorship received. Conclusions This study describes the prevalence and predictors of burnout among physicians prior to the COVID-19 pandemic. Predictors that are potentially modifiable at local practice and systems levels include job satisfaction, workplace quality, hours worked, and mentorship received. New family physicians (≤5 years in practice) were at increased risk of depersonalization; strategies specific to this group may limit burnout and address the healthcare workforce crisis. Periodic studies are recommended to identify the impact of strategies implemented, emergent predictors, trends, and mitigating factors associated with burnout. The current crisis in family medicine indicates an urgent need to look back and plan forward.